Revealed Comparative Advantage of Pakistan's Agricultural Exports - World Bank (Washington, DC, 2013)
Pakistan is widely believed to be underperforming as far as its agricultural export potential is concerned. However, analyses to support this allegation are very few, in part due to the lack of easily accessible data. In this paper provide the first necessary step in the analysis of Pakistan's comparative advantage in agricultural export markets. However, little or no analysis has been done that sheds some more light on this issue, in the sense of better specifying in which commodities and which markets Pakistan's comparative advantage is strongest. This paper attempts to start filling that void by quantifying the degree of comparative advantage of Pakistan agricultural export products in major overseas markets. This quantification is a necessary first step in getting a better handle on the factors that may limit the extent to which Pakistan is able to enter markets where it has a comparative advantage. Expansion of Pakistan's share in overseas export markets is crucial for further development of the country's agricultural sector. The main objective of the paper is to identify products where Pakistan has demonstrated comparative advantage, and to provide a first step towards understanding the factors that at present limit possibilities for further exploiting that advantage. The paper analyzes actual export flows and calculates measures of revealed comparative advantage. The focus in this paper being on agricultural trade, the analysis is based on international trade data that incorporates a unique degree of detail not seen before in trade analyses for Pakistan.